Music and Liturgy in the IECLB – Evangelical Church of Lutheran Confession in Brazil - de Souza, João Carlos; Wanke, Roger Marcel (Vox Scripturae - Revista Teológica Internacional, 2018)
An important element in the worship service of the main Christian denominations, music finds its place in liturgy based in traditions that remain from Ancient Israel. Music appears unequivocally as an element in God´s worship in the Old Testament. There are safe indications, especially in pauline letters, that it was also a part of the worship in primitive Christian communities. However, the absence of more explicit biblical orientations concerning the use of music in liturgy has led to a diversity of attitudes concerning its reception in different Christian traditions, going from its rejection by the Ancient Church to its pedagogical use in reformatory worship. As a church coming from the Reformation, the Evangelical Church of the Lutheran Confession in Brazil (IECLB) has received a rich liturgical and musical tradition, which is being actualized according to the different contexts in which it is lived. The plurality of intra-eclesiastical traditions, embodied in different theological, liturgical and hermeneutic emphasis, also reflects in the different uses of music in the worship service. Despite this, there are principles extracted from the Bible and the lutheran tradition that must be valued for a healthy musical and liturgical practice in the context of the many traditions present in IECLB.
Keywords: Liturgy; Christian service; Music; Lutheranism